On the centrality of peripheral research and the dangers of tight boundary gatekeeping. (May 2021) - Gendron, Yves; Rodrigue, Michelle
Abstract: Drawing on a literature-based analysis and our own experiences in doing work at the periphery of accounting research, this essay aims to reflect on the processes by which accounting research boundaries are socially constructed, henceforth demarcating a division between center and peripheral research. Recognizing that serious indications of tight boundary gatekeeping are on the rise in the accounting research domain, we highlight the extent of negative consequences ensuing from this kind of behavior. We also maintain how, collectively speaking, we may gain from developing more receptive attitudes toward the peripheral. Along with several other writers, we view work at the periphery of an area's research boundaries as having significant potential for the development of new ideas and innovations. However, an excessively protective center may prevent these ideas and innovations from being brought into the field of visibility, especially when the center is inclined to issue stringent reviews and this degree of stringency, somehow, reverberates in peripheral journals' reviewing practices. We believe that the longer-term sustainability of accounting research requires the incremental development of spaces of receptivity toward the unexpected and peripheral.